GROSS MASS, PAYLOAD AND CARGO SECURING DEVICES IN TWENTY-FOOT AND FORTY-FOOT GENERAL PURPOSE MARITIME CONTAINERS - Jagelčák, Juraj; Fazekaš, Miroslav; Vrábel, Ján (Doprava a spoje, 2012)
The cargo must be appropriately secured during the carriage in maritime containers to withstand normal transport conditions during combined transport (road, rail and sea). The article presents the results of analysis of cargo securing equipment in twenty foot and forty foot general purpose maritime containers of type 22G0, 22G1, 25G1, 42G0, 42G1, 45G0 and 45G1.